Drystone walls in the Algarve, Portugal. Characterization and interconnection with the geology and lithology - Feroldi, Ada (2021)
Drystone walls can be frequently observed along the Algarve, south region of Portugal, performing both support and property division. This region is also known by its geological diversity and, consequently, lithology, which are intimately related to the orography. The combination of all these factors allowed the proliferation of this traditional drystone walls during the last centuries, and they represent not only an important element of the landscape, but also a perspective of the social, economic and technical bases of Algarve’s heritage. This article intends to present this diversity and the relationship between its various facets. In order to achieve the objectives, several field surveys were carried out to different geological zones, with the intention of gathering information related to the natural material used and its construction technique, as well as interaction with local inhabitants. These visits were supported by bibliographic and “Web-graphic” research, to substantiate the hypotheses. Based on the data results it is possible to identify a close interconnection between the geology and wall structure typology, since they are made with the natural rock fragments (raw material) found nearby. However, its function is more related to the orogeny and lithology, the latter defining also the type of agricultural culture. The study is enriched by the enormous diversity of rock types, although the Algarve is a relatively small region. The main limitations found during the development of the study are related to the physical access to the walls and the interviews with the locals. These constrictions were due to the lack of land maintenance, allowing vegetation to growth naturally, invading and covering the walls, and also due to the pandemic situation brought by the COVID-19 virus, which interdict the interaction between persons and also the travels. Despite the restrictions mentioned, the fieldtrips gave enough data to support the correlation between the geology, lithology and the raw material used on the drystone walls, as well as their relation to the terraces that proliferate in specific areas of Algarve. In view of the scarcity of bibliographic elements associated with this subject, in the studied territory, the elaboration of documents that allow the identification, characterization, geo-location and dissemination of the object of study, is considered as an asset for this theme. Finally, the study aims to alert and counter the tendency to abandon this type of heritage, valuing it and making it known.